Shifting and change in the medium of instruction from Bahasa Malaysia to English in Science and Mathematics / Krishna Samy Nallasamy - Nallasamy, Krishna Samy (2005)
The change in the medium of instruction from Bahasa Malaysia to English in the teaching of Science and Mathematics in the Malaysian education system by the government in 2004 has drawn much controversy both from academicians and politicians. Some fear this change will erode the role of Bahasa Malaysia as the national language and, secondly, the national language will not be able to develop as a dynamic language to be used in mathematics and sciences. However, it is pointed out that while inherent weaknesses in Bahasa Malaysia fails to provide the knowledge and information in mathematics and sciences, English must be adopted so that Malaysian students will be able to compete in the field of sciences in the face of the globalize world. This change does not diminish the role of Bahasa Malaysia as the national language, which acts as the catalyst in the nation building while English language is used as a tool to enhance the learning and teaching of science and mathematics.